Istikhdâm al-Waṣîlah al-Ta’lîmiyyah Appy Pie li Tarqiyyah Mahârah al-Kitâbah - Aulya Fa’ikoh, Ela; Azhari, Saefullah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Purpose- This article aims to explain the results of study on the use of Appy Pie learning media, as well as to determine the effectiveness of Appy Pie learning media to increase maharoh kitabah of grade 8 students of MTs N 1 Tuban. Design/Methodology/Approach The quantitative method was applied in this study. A total of 31 students of grade 8 at MTs N 1 Tuban participated in the study. The data was obtained through interview, observation, test and documentation at MTs N 1 Tuban. Findings— During the process of learning Arabic, especially maharoh kitabah, the students have not been able to write Arabic sentences properly and correctly. The results of this study indicated that the average value of grade 8 at MTs N 1 Tuban before the application of the Appy Pie learning media is 56, while the average value of the students after the application of the Appy Pie learning media is 82. As a result, the Appy Pie learning media is effective for increasing maharoh kitabah for grade 8 students of MTs N 1 Tuban, as well as teaching Arabic maharoh kitabah. Because this media presents new innovations, so learning is not always monotonous using books, but changes learning media with a touch more modern using this medium. Research Limitation/Implications- Due to time limits, this study could not go any further, however, it obtained satisfactory results and is expected to help develop writing skills learning innovations at MTs N 1 Tuban